Structured catalysts containing Co, Ba and K supported on modified natural sepiolite for the abatement of diesel exhaust pollutants - Milt, Viviana Guadalupe (2010)
Natural sepiolite-supported catalysts, structured as highly porous ceramic discs were investigated for their application in diesel exhaust after treatment. Catalysts containing cobalt, potassium and barium, which are active ingredients for diesel soot combustion and NOx adsorption, were prepared by wet impregnation of the support materials. The influence of incorporating CeO2 as additive to the clay (sepiolite), along with activated carbon as pore generating agent (PGA) which is eliminated during the heat treatment step was studied. The additives affect the textural properties of the discs, that are related with their permeability and filtering capacity, but do not significantly alter their catalytic properties when Co and K are present as the active ingredients. The solids were characterised by several techniques: N2 adsorption, mercury intrusion porosimetry (MIP), TGA-DTA, TPR, XRD and SEM. Different weight losses were observed as the temperature increased in TGA-DTA experiments owing to dehydrations and dehydroxylations of the sepiolite structure. The maximum rate of soot combustion for the Co- and K-containing catalyst was 366 and 453 °C for tight and loose contact, respectively. The bare sepiolite practically does not interact with NO + O2, however, the addition of potassium and/or Ba caused a notable increase in the NOx adsorption capacity. The catalytic activity results for the Co,K/sepiolite system and the excellent rheological properties of pastes that allow extrusion in various shapes which on heat treatment leads to conformed ceramic bodies with high mechanical strength, thermal resistance and large surface areas make this material an interesting potential candidate for the development of catalytic filters for diesel exhaust abatement applications.